Essential skills in call classes:Enhancing searching and language skills. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
In the quest of making learning more relevant in the contemporary era of information and communication technology, the Internet is considered a valuable resource to both language teachers and learners in computer assisted language learning (CALL) contexts (Singhal, 1997).